INTRAUTERINE GROWTH RESTRICTION AND ITS RELATIONSHIP WITH COVID-19 AND DENGUE DURING PREGNANCY: CASE REPORT - Pinto, Amanda Està©phane da Costa; de Andrade, Ana Clara Rosa; Rizzo, Beatriz Rocha; Siqueira, Maria Júlia Duarte; Cardoso, Nathalia Da Mata (CIPEEX, 2022)
INFECTIONS DURING PREGNANCY ARE KNOWN TO IMPAIR ITS COURSE, AND CAN HAVE NUMEROUS MATERNAL-FETAL OUTCOMES. RECENTLY, NEW VIRUSES HAVE EMERGED, WHOSE PATHOGENIC CHARACTERISTICS DURING THE GESTATIONAL PERIOD ARE NOT COMPLETELY UNDERSTOOD, AMONG THEM IT IS POSSIBLE TO HIGHLIGHT SARS-COV-2, WHICH CAUSES COVID-19. ANOTHER INFECTION THAT HAS A DIRECT INFLUENCE ON THE GESTATIONAL PERIOD IS DENGUE, WHOSE SEVERITY IS DIRECTLY RELATED TO MATERNAL AND FETAL COMPLICATIONS. THUS, THE STUDY AIMS TO REPORT THE CASE OF A PATIENT WHO DEVELOPED INTRAUTERINE GROWTH RESTRICTION AFTER INFECTION WITH COVID-19 AND DENGUE DURING PREGNANCY. PATIENT, FEMALE, 25 YEARS OLD, WITHOUT COMORBIDITIES, PRIMIGRAVIDAE, ASYMPTOMATIC, ATTENDS THE OBSTETRIC EMERGENCY FOR FOLLOW-UP OF IUGR (INTRA UTERINE GROWTH RESTRICTION). IT PRESENTS A HISTORY OF INFECTION BY COVID-19 WITH A GA OF 20 WEEKS AND 5 DAYS AND FOR DENGUE WITH A GA OF 24 WEEKS AND 5 DAYS. PATIENT RETURNS FOR INVESTIGATION OF THROMBOPHILIA, SINCE THE USG OF THE CORRESPONDING DAY SHOWED ABNORMAL PLACENTAL FLOW WITH RESISTANCE TO THE LEFT. CESAREAN DELIVERY WAS PERFORMED WITH GA 35 WEEKS + 1 DAY, PRETERM NEWBORN WITH BIRTH WEIGHT OF 1590G (SGA), REFERRED TO THE ICU DUE TO LOW WEIGHT, PREMATURITY, FOR INTENSIVE CARE. DURING THE CESAREAN SECTION, THE PATIENT’S PLACENTA WAS SENT FOR ANATOMOPATHOLOGICAL ANALYSIS IN WHICH THE DIAGNOSIS OF PLACENTAL THROMBOSIS WAS CONFIRMED. NB REMAINED HOSPITALIZED FOR 16 DAYS TO REACH THE MINIMUM WEIGHT ESTIMATED BY THE PEDIATRICIAN OF 1800G. CURRENTLY, THE PATIENT AND THE NB ARE AT HOME, STABLE AND UNEVENTFUL. INFECTION OF PREGNANT WOMEN WITH COVID AND DENGUE CONCOMITANTLY IS AN EXTREMELY RARE EVENT IN CLINICAL PRACTICE. THE STUDIES REFLECT THE VAST OUTCOMES THAT CAN BE PRESENTED IN THE FACE OF DENV AND SARS-COV-2 INFECTION DURING THE GESTATIONAL PERIOD, WHICH ARE CRUCIAL FOR SATISFACTORY FETAL DEVELOPMENT.